Unusual cause of haemolytic anaemia: Glucose phosphate isomerase deficiency - Mukesh Dhankar; Piali Mandal; Robin Singh (Elsevier, 2024)
Introduction: Glucose phosphate isomerase (GPI) deficiency is a rare autosomal recessive disorder that causes hereditary nonspherocytic hemolytic anemia (HNSHA). It is caused by homozygous or compound heterozygous mutation of the GPI gene on chromosome 19q13. Approximately 57 GPI mutations have been reported at the molecular level. Case report: A 4-years and 6-month-old boy presented with progressive pallor along with multiple blood transfusion requirements since four months of age. He had hemolytic anemia associated with macrocytosis, reticulocytosis, neutropenia, and hyperbilirubinemia. Whole-exome sequencing showed that he carried a specific variant in the GPI gene, denoted as c.1040G > A p.Arg347His, which is a homozygous autosomal recessive inherited pathogenic mutation found in exon 12. Conclusion: This report highlights the clinical features and molecular etiology of an Indian patient with GPI deficiency, a rare cause of hereditary hemolytic anemia. A specific variant in the GPI gene was identified through whole-exome sequencing, which is linked to HNSHA. Patients with GPI deficiency require medical management during childhood to monitor for potential complications and prevent hemolytic crises. With optimal management, patients with GPI deficiency can lead a relatively healthy life with normal expectations of growth and development.